Promoting Everyday Philanthropy: A Study of Retail Partnership and Baznas (National Amil Zakat Agency) in Indonesia - Budiman, Arief; Setiawan, Fitriansyah Agus; Fitri, Laily Nur (STAI Publisistik Thawalib Jakarta, 2026)
This study identifies key barriers to retail-based donation systems in Indonesia, including low trust, limited zakat literacy, digital security concerns, and perceived intrusiveness, which significantly reduce donation effectiveness. It aims to analyze the Alfamart–BAZNAS partnership in enhancing effortless donations through improved accessibility, transparency, trust, and social awareness embedded in daily shopping activities. A qualitative case study approach was employed, using semi-structured interviews, field observations, and document analysis, with thematic analysis to identify factors influencing consumer participation in retail donation programs. Findings reveal that integrating donations into Alfamart shopping transactions significantly increases consumer participation. Key drivers include cashier-based convenience, small donation amounts, and extensive store coverage. Program transparency through public reports, social media, and in-store displays strengthens consumer trust, while social impact awareness and visual communication at checkout points reinforce donation intention. The Alfamart–BAZNAS collaboration creates a simple, fast, and accessible philanthropic model that sustains consistent public contributions. The study further shows that cashier-led donation requests strongly enhance participation by serving as behavioral triggers that generate positive social pressure and trust. Empirical data from 2024–2025 confirms steady growth, reaching IDR 21.7 billion, highlighting the dominance of interpersonal communication despite minor monthly fluctuations. Retail partnerships are effective in increasing donations through seamless daily shopping integration, transparency, and enhanced public participation. This study contributes to the development of scalable, transparent, and replicable retail-based philanthropy models.